Systematic review of climate change induced health impacts facing Malaysia: gaps in research - Raksha Pandya-Wood; Azliyana Azhari; Hamimatunnisa Johar; Adeline Johns-Putra; Nurfashareena Muhamad; Tin Tin Su (IOP Publishing, 2024)
In Malaysia, climate change typically manifests as frequent and extreme weather events. The effects on human health of such meteorological and ecological imbalances are multiple and diverse. Urgent attention is needed to address the health-related threats facing Malaysia as a result of climate change. This systematic review (SR) of available evidence adopted Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and identified and assessed a broad range of English language empirical, published research and excluded grey literature. Bias and quality of articles was assessed using Mixed Methods Assessment Tool. Using the search engines Scopus, PubMed, Ovid EMBASE, Web of Science, and EBSCO Host Medline, n = 374 results were yielded. Of these, after checking, n = 23 studies were examined. The studies can be grouped into three climatic themes Exposure , Outcomes and Planning . Our review confirms that urgent funding and investment is needed for larger-scale intervention studies on each of these themes. We observed a scarcity of high-quality empirical research, a preponderance of modelling studies to project and simulate scenarios, and a limited number of qualitative studies. Particular gaps in knowledge exist on climate change impacts on health in population groups in terms of demographic intersections to support these epidemiological data and simulation pathways. Furthermore, there was an absence of data on various topics concerning the effects of climate change on, for example, mental health, women, older people and/or the effects of displacement. The limitations of this work include accepting only English language publications and presenting only empirical studies. The study was not funded but was managed by the Monash Climate Change Communication Research node. This SR was registered on PROSPERO ID: CRD42023431868.